The Effects of Online Stress Coping Course on Student Nurses' Perceived Stress and Automatic Thoughts - Didem Ayhan; Hilal Seki Öz (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
It is very important for nursing students to manage stress effectively, because of the stress caused by the individual problems and the negative consequences reflected in the interaction with the patient. This study analyzed whether the ‘coping with stress’ online course had any effect on the perceived stress levels and automatic thoughts of nursing students based on their behavioral patterns (A or B). This pretest-posttest quasi-experimental research was conducted with 90 students. Data were collected online, using a Personal Information Form, the type-A Personality Scale, the Perceived Stress Scale-10, and the Automatic Thoughts Questionnaire. Descriptive statistics and dependent samples t-test were used in the data analysis. Of the participants, 53.2% had type-A and 46.7% had type-B personalities. After the course, there were significant decreases in mean perceived stress scores of type-A and all nursing students and mean automatic thoughts scores of type-B and all nursing students (p